Key Aspects of German Business Law
XXIV, 522 p.
Keywords: This book presents a clear and precise overview of the key aspects of German business law. It was written by attorneys involved in the daily practice of bu- ness law in Germany and is aimed at people who wish to orient themselves quickly with the German legal system and the manner in which it impacts bu- ness purchases, establishment, operations and liquidations. The first section of the book is devoted to an explanation of the major issues to be considered in acquiring or establishing a business in Germany. The second section focuses on areas of commercial law that are important for an operating business. In comparison to the last edition four new areas (transportation law, customs regulations, insurance law and state liability law) are treated. The f- lowing sections deal with labor law as an independent part of German business law and with computer law. Furthermore, procedural law and European law are addressed. Finally, the last two sections of the book are devoted to an overview over the German tax law, which has an enormous impact on business decisions, and IP law. In all sections special attention has been paid to highlighting and explaining the differences between the German legal system and that of the United States. Nevertheless, the intention is to provide information that will prove valuable to all foreigners, particularly business men and women and lawyers advising clients with an interest in doing business in Germany.